The role of adopting Islamic accounting standards AAOIFI in eradicating accounting illiteracy and promoting Islamic investments - an exploratory study of a sample of Islamic economic units - Ilham Wathiq (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The objective in this study involves demonstrating the importance in the role of Islamic economic units in eradicating accounting illiteracy, because the adoption of specific basics can enhance transparency and contribute to improving the level of financial reporting, which enhances confidence between investors and customers and thus facilitates decision-making and enables shareholders through informed decisions based on accurate financial information provided by those units, which achieves sustainable economic development and enhances the ability of those units to adapt to economic and social variables as The adoption of these units of Islamic accounting standards based on the principles of Islamic Sharia will help enable individuals working in these units and stakeholders to understand the principles of Islamic accounting and associated standards and then direct them towards correct investment decisions, this research used the deductive approach in the theoretical side and the inductive approach in the practical side by preparing a survey list for a sample of workers in Islamic economic units as well as investors and stakeholders, as the sample included 70 forms that were analyzed statistically. Using the SPSS program, it was concluded that there is a role for the adoption of Islamic economic units of AAOIFI standards in the eradication of accounting illiteracy and its reflection on investment decisions, and the research recommends the need to pay attention to important methods and procedures in promoting accounting literacy in Islamic economic units through the organization of workshops and training courses for employees.Establishing educational curricula commensurate with their needs, cooperating with educational institutions, and preparing partnerships with universities and institutes to provide specialized educational programs to support this field, as accounting literacy in Islamic economic units needs integrated efforts based on activating Islamic accounting standards, which contributes to achieving sustainable development and enhancing economic performance.